AIR TEMPERATURE AND HUMIDITY DATA LOGGERS EQUIPPED WITH LABVIEW AND ARDUINO-BASED WARNING SYSTEMS - Akhmad Solikin; Karman (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2022)
In the industrial world the process of measuring air temperature and humidity is a very important measurement process in the production process. But in practice in the field, the process of measuring air temperature &humidity is mostly done manually, which is done by recording which has the disadvantage of inaccurate measurement data. Recording temperature measurements that are done manually causes the product results to be not good, both in terms of quantity and quality. Related to these problems, the author took the initiative to create an alternative data logger device that is simpler, easier to integrate and relatively more affordable, without reducing the value of measurement accuracy. This data logger tool functions to monitor air temperature and humidity in real time, whose monitoring results are displayed through a system interface with the help of Labview software, Arduino Uno & DHT sensor. The final results of the trial design of the data logger tool are able to & have advantages, among others, air temperature and humidity parameters can be monitored automatically accompanied by alarm notifications, air temperature and humidity data parameters can be recorded automatically into logging data in the form of MS Excel format, and user can analyze data on air temperature and humidity parameters and the final results of the trial This air temperature & humidity data logger tool has an error rate of 0.5%.